UJI FISIK DAGING DOMBA DIMARINASI DENGAN EKSTRAK BUNGA KECOMBRANG - Muhammad Raihan Fadhillah Berky (Bajang Institute, 2024)
The research objectives were to determine the effect of the use of kecombrang flower extract on the water water binding capacity, pH, and cooking shrinkage of lamb meat. Data were analyzed by variance analysis with parameters of cooking shrinkage, pH and water binding capacity. The design used was a nonfactorial completely randomized design (CRD) with 4 treatments and 5 replicates. With treatment levels P0 = control (without using kecombrang flower extract), P1 (marination of kecombrang flower extract 100 gr/100ml water), P2 (marination of kecombrang flower extract 200 gr / 100 ml of water), P3 (marination of kecombrang flower extract 300 gr / 100 ml of water). Based on the results of this study, the use of kecombrang flower extract gives no significant effect on the physical test of lamb meat, namely on cooking shrinkage, pH and water binding capacity